2009
DOI: 10.1111/j.1745-4557.2009.00281.x
|View full text |Cite
|
Sign up to set email alerts
|

QUALITY CHANGES IN FRESH CHIVES (ALLIUM SCHOENOPRASUM L.) DURING REFRIGERATED STORAGE

Abstract: This study investigates quality changes in fresh chives stored at 0 and 4C during 21 and 14 days, respectively. The product was packaged in trays and covered with polyvinyl chloride films. Weight loss, surface color, total chlorophyll, carotenoids, reducing sugars and browning potential were evaluated in order to determine shelf life at each temperature. In addition, internal atmosphere composition, total phenolics, radical scavenging activity and ascorbic acid content were measured for samples stored at 0C. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
4
1
1
Order By: Relevance
“…Moreover, chives leaves seem to be relatively abundant in pigments in comparison to other studied Allium plants. However, our reports for total chlorophylls in chives leaves were higher than 1.2 mg/g dw (Viña and Cerimele, 2009). Only, Egert and Tevini (2002) found higher total chlorophylls in chives leaves (6.7 mg/g dw).…”
Section: Total Chlorophylls and Carotenoidscontrasting
confidence: 77%
“…Moreover, chives leaves seem to be relatively abundant in pigments in comparison to other studied Allium plants. However, our reports for total chlorophylls in chives leaves were higher than 1.2 mg/g dw (Viña and Cerimele, 2009). Only, Egert and Tevini (2002) found higher total chlorophylls in chives leaves (6.7 mg/g dw).…”
Section: Total Chlorophylls and Carotenoidscontrasting
confidence: 77%
“…Storing mint samples at 0 °C caused a low production of CO 2 from the respiratory activity of the packaged product that did not allow a greater accumulation of this gas inside the trays, added to a relatively high permeability of the film used. Similarly, when analysing the composition of the internal atmosphere in trays containing fresh-cut chives covered with PVC and stored at 0 °C for 17 days, Viña and Cerimele (2009) found that CO 2 concentration increased significantly on the second day and then remained constant until the end of the storage.…”
Section: Resultsmentioning
confidence: 94%
“…Viña and Chaves (2006) pointed out that total phenol content in fresh-cut celery did not change significantly during 28 days of storage at 0 °C. In contrast, for chives stored at 0 °C for 13 days, total phenolic content remained constant until day 6, when there was an increase of 12% over the initial content (Viña & Cerimele, 2009). In minimally processed carrots stored for 12 days at 15 °C, Basilio Heredia and Cisneros-Zevallos (2009) reported that the intensity of the mechanical damage exerted on the product (whole, sliced or grated carrots) played a decisive role in the activation of the synthesis and the accumulation of phenolic antioxidant compounds.…”
Section: Total Chlorophyll and Carotenoid Contentmentioning
confidence: 82%
See 1 more Smart Citation
“…Juntamente com a acidez, faz-se necessária a determinação do pH, que é um parâmetro indicativo da susceptibilidade ao desenvolvimento de micro-organismos e também associado a palatabilidade, já que correlaciona-se inversamente com a acidez. Alguns trabalhos têm descrito a importância da quantificação dessas variáveis físico-químicas em hortaliças folhosas (BRUECKNER; PERNER, 2006;MIGUEL;DURIGAN, 2007;REIS et al, 2014;SANTOS et al, 2014;VIÑA;CERIMELE, 2009). …”
Section: Introductionunclassified